PENGARUH KUALITAS PRODUK DAN MEREK TERHADAP KEPUTUSAN PEMBELIAN AIR MINUM DALAM KEMASAN (AMDK) MEREK AYIA - -, Misharni (LPPM Universitas Muhammadiyah Sumatera Barat, 2017)
This study aimed to determine the effect of product quality and merk on purchase desicion (AMDK) at STIE Sumbar Pariaman. This study included survey research obtained by questionnaire. Population in this study are student 2016 year as many as 1400 people at STIE Sumbar Pariaman. Samples used research as many as 100 respondent. The analytical methods used multiple linear regression. The results of this study indicate that (1 ) Multiple linear regression is Y=1,679 +0,200 X1+0,346 X2, quality product and merk influential in purchase decision of customer is 0,200and followed by merk is 0,346. (2) Quality product significant effect of purchase decision at Student STIE Sumbar Pariaman, because value t count is 2,986 with a significant level of 0,004<0,05. And merk significant effect of repurchase intention at Student STIE Sumbar Pariaman because value t count is 4,601 with a significant level of 0,000>0,05. (3) The value of the R Square (R2) quality product and merk of purchase decision at Student STIE Sumbar Pariaman is 23,7% while the rest is 76,3% influenced by other than the model under study as price, packaging and others. Keywords :Product Quality; Merk; Purchase Decision.